Adapting ICT in higher education in the developing world: influencing dynamics. (9th August 2019) - Remache, Abdelghani; Belarbi, Abdelhafid
The frenzy of information and digital communications marked the 21st century by modernising societies and levering living standards. Policy makers of all economic spheres in the developed world reckon that information and communication technology (ICT) investment fosters economic development and performance. Recent studies in the USA and Europe indicate that investing in ICT helps achieve high growth rates in every sector of the economy. Building on recent literature reviews, this paper argues for the importance of ICT integration in higher education institutions (HEIs) in the developing world and proposes some of the major influencing factors that can help translate ICT integration into reality and serve as a major stimulant for economic development. The paper also reveals how investing in ICT enhances economic performance while focusing on the specific opportunities and the challenges obstructing the acquisition and adoption of ICT by the developing nations.